The neverending runtime: Using new technologies for ultra-low power applications with an unlimited runtime - Cassens, Björn; Martens, Arthur; Kapitza, Rüdiger (International Conference on Embedded Wireless Systems and Networks, 2016)
Many wireless sensor network scenarios dictate tight node size and weight limits. Still a long, if possible infinite, mission lifetime is demanded. To fulfill these contradicting requirements, we propose ECON1 a tailored combination of an energy harvesting device with a new nano-power sleep mode that requires near zero power and preserves the application state. An operating system agnostic system software layer combined with NVRAM enables lightweight mode transitions between nano-power sleep mode and normal operation. Furthermore, by introducing a new ultra-low power management circuit we can tolerate power outages that may occur when the power consumption outperforms the harvested energy. ECON has been evaluated using a Texas Instruments MSP430 node equipped with non-volatile FeRAM. Our nano-power sleep mode drains 3.7 times less power than the best onboard available sleep mode. Entering and leaving this mode is worthwhile when the microcon-troller idles for more than 1.01 ms.
CRIS-Team Scopus Importer:2022-07-19
Keywords: Energy Aware Systems; Energy Harvesting; Firmware; Operating Systems; Power Outages; Wearable